Analysis of risk factors of mild cognitive impairment - Janoutová, Jana; Ambroz, Petr; Zatloukalová, Anna; Machaczka, Ondřej; Kovalová, Martina; Němček, Kateřina; Janout, Vladimír (Profese Online, 2020)
Background: Term of Mild Cognitive Impairment has been introduced in 90 ies. It is described as transitional phase between normal aging and dementia. According to the development of age structure of population, diseases with alterd cognition are coming into the interesss of specialists as well as society. Aim: Paper presents basic problems of Mild Cognitive Impairment as well as selected results of epidemiological case-control study which try to ascertain risk factors responsible for transition of Mild Cognitive Impairment into Alzheimer´s Disease. Methods: Questionaire investigation and taking sample of blood for genetic analysis. Final statistical evaluation. Results: 219 cases and 479 controls were evaluated. There were more females (1.7) with cognitive impairment compare to male. More people in control group perform intellectual work compare to cases. There were more ischemic disease of lower limbs in group of cases compare to controls. All findings were statistically important. There were found statistically significant difference in genes TOMM40, IDE and CLU. Conclusions: Taking into consideration that amnestic form of Mild Cognitive Impairment is initial phase of dementia (mainly Alzheimer´s Disease) then presumably development of Mild Cognitive Impairment is influenced by same risk factors. Knowledge ot those risk factors may help in prevention and early detection both Mild Cognitive Impairment and dementia.
Keywords: dementia; mild cognitive impairment; risk factors